2010
DOI: 10.1158/0008-5472.can-09-0761
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of RON Receptor Signaling Promotes Apoptosis and Gemcitabine Sensitivity in Pancreatic Cancers

Abstract: The RON receptor tyrosine kinase is overexpressed in premalignant pancreatic intraepithelial neoplasia (PanIN) and in the majority of pancreatic cancers. In pancreatic cells, RON is an important K-Ras effector and RON ligand can enhance migration/invasion and apoptotic resistance. However, the pathobiological significance of RON overexpression in pancreatic cancers has yet to be fully established. In this study, we demonstrate that RON signaling mediates a unique transcriptional program that is conserved betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 34 publications
3
99
0
Order By: Relevance
“…Previous studies have shown that RON is overexpressed and activated in primary PDAC samples and established cell lines (1)(2)(3)(4)(5)(6). Here, we determined the therapeutic effect of BMS-777607 on RON signaling in L3.6pl cells and CSCs þ24/44/ESA .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that RON is overexpressed and activated in primary PDAC samples and established cell lines (1)(2)(3)(4)(5)(6). Here, we determined the therapeutic effect of BMS-777607 on RON signaling in L3.6pl cells and CSCs þ24/44/ESA .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant RON expression also regulates PDAC cell migration, survival, and invasion through multiple signaling pathways (4-6, 9, 10). In certain PDAC cell lines, knockdown of RON expression by specific siRNA causes PDAC cell apoptosis and increase their sensitivity in response to chemotherapeutics (4). These preclinical studies indicate that aberrant RON signaling is critical for PDAC cell growth and survival.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The RON gene encodes the macrophage-stimulating protein (MSP) 1 receptor (1). The activation of RON by MSP induces tumor progression and invasion, whereas the inactivation of RON promotes cell apoptosis (2)(3)(4). RON is a heterodimeric protein with a disulfide bond linking a 40-kDa α chain, containing the extracellular domain for ligand binding, and a 150-kDa β chain, incorporating the intracellular kinase domain and a transmembrane domain (5,6).…”
Section: Introductionmentioning
confidence: 99%